The Multiple Meanings of the Shona Traditional Performance Theatre (dariro): Unpacking the Concept - Matiure, Perminus (Cultural Arts Research and Development, 2024)
The paper discusses the multiple meanings of the Shona traditional theatre, commonly known as dariro. In this paper, dariro is taken to refer to traditional theatre in which socialization, singing, instrument playing, incantations, dance and other artistic skills are enacted, especially during social or religious events. The data that furnishes this paper was collected from the Shona people using a qualitative ethnographic methodology in which Shona culture bearers from Mashonaland East Province of Zimbabwe were consulted in order to solicit information concerning the nature, aesthetic functions, and dynamics that surround the concept of dariro. The data gathered during the fieldwork indicated that dariro is perceived as a traditional theatre designed to create space for individuals or group performance, especially in dance, poetry, or singing. The traditional theatre was also viewed as the social platform on which the Shona epistemic and ontological philosophy of life, chivanhu is enacted. The findings also indicated that the events that unfold within the confines of dariro, are characterised by timelessness, team work and events that are aesthetic and socially conjugal. Dariro can be created in an open space or under a tree depending on the nature of the context, or can be constructed inside a traditional hut, banya with participants demarcating the boundaries to create the inner chamber in which events are presented. The paper concludes that dariro is pivotal in collectively drawing the participants’ attention towards one unity of purpose. As such, it acts as a platform where social, physical, and religious forces converge.